Building Resilience in High Technology Projects: An Integrated Multi Framework Risk Management Approach - Mubarok, Ahmad; Yuda, Fardan Zeda Achmadi (Novatio : Journal of Management Technology and Innovation, 2025)
High-technology projects face rapidly evolving risks across technical, organizational, and regulatory domains, creating challenges that single-framework governance often cannot fully address. This study proposes an integrated multi-framework risk management approach, combining governance-level (e.g., ISO 31000), domain-specific (e.g., ISO/IEC 27005, NIST SP 800-53, NIST AI RMF), and execution-level tools (e.g., SAFe ROAM, NASA NPR 8000.4C). Unlike prior studies that apply frameworks in isolation, this research evaluates a layered integration model designed to improve risk coverage, mitigation speed, and compliance readiness. Using framework mapping, Fuzzy Multi-Criteria Decision Making (MCDM), House of Risk (HOR) analysis, and Monte Carlo simulations, the findings show that integrated governance achieves broader protection, reduces closure times for high-velocity risks, and raises audit pass rates above 90%. The novelty of this study lies in offering a practical governance blueprint that reconciles overlapping standards while tailoring protections for AI, cloud computing, and mission-critical systems. Beyond technical improvements, the model aligns organizational risk appetite with operational practices, fostering resilience and agility.